2005
DOI: 10.1111/j.1476-4431.2005.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of acyclovir in adult horses

Abstract: Objective: To determine the pharmacokinetics of acyclovir administered intravenously (IV) and orally to healthy adult horses. Design: Random cross-over with an approximate 1-week washout period between trials. Setting: University veterinary medical teaching hospital. Animals: Six healthy adult research herd horses. Interventions and main results: Acyclovir was administered IV (10 mg/kg in 1 L isotonic crystalloid solution over 60 minutes) and orally (20 mg/kg) to healthy adult horses. Plasma samples were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 22 publications
4
42
0
Order By: Relevance
“…The peak concentrations after i.v. acyclovir administration were similar, i.e., 10.7 g/ml in this study versus 10.4 g/ml in the study of Wilkins et al (30). The mean AUC in this study (18.0 g ⅐ h/ ml) was also similar to the one reported by Wilkins et al (30) (19.2 g ⅐ h/ml), together with other PK parameters, such as total body clearance and the apparent volume of distribution at steady state.…”
Section: Vol 51 2007 Pharmacokinetics Of Acyclovir In Horses 4311supporting
confidence: 55%
See 2 more Smart Citations
“…The peak concentrations after i.v. acyclovir administration were similar, i.e., 10.7 g/ml in this study versus 10.4 g/ml in the study of Wilkins et al (30). The mean AUC in this study (18.0 g ⅐ h/ ml) was also similar to the one reported by Wilkins et al (30) (19.2 g ⅐ h/ml), together with other PK parameters, such as total body clearance and the apparent volume of distribution at steady state.…”
Section: Vol 51 2007 Pharmacokinetics Of Acyclovir In Horses 4311supporting
confidence: 55%
“…However, as the t 1/2 of elimination was expressed as a harmonic mean in both studies and as large variations were noted among the various horses in our study, we can presume that these differences are not significant. Wilkins and colleagues (30) were unable to calculate the PK parameters after p.o. administration of acyclovir, as the plasma concentrations were below the lower limit of detection in all animals (LOQ, 156 ng/ml).…”
Section: Vol 51 2007 Pharmacokinetics Of Acyclovir In Horses 4311mentioning
confidence: 99%
See 1 more Smart Citation
“…As acyclovir is from patent since 1997 and generic alternatives are available, it seems attractive to use this drug for the treatment of horses during an outbreak. Previous studies (Wilkins et al, 2005) indicated that twice daily IV infusions of acyclovir (10 mg/kg) results in plasma concentrations above EC 50 -levels during the entire treatment interval. However, the EC 50 -value reported in their study was 0.3 mg/ml, which is 10-fold lower than the one we found.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment might have been not effective due to the reported poor bioavailability of 305 acyclovir (3-8%) (Wilkins et al, 2005, Bentz et al, 2006, Garré et al 2007 (Hart et al, 2008) and in some cases -as case 5 -an association between EMPF and 339 immunosuppression seems to be obvious.…”
mentioning
confidence: 99%